Are acoustical parameters of begging call elements of thin-billed prions related to chick condition? - Quillfeldt, Petra; Poisbleau, Maud; Mundry, Roger; Masello, Juan F.; Justus Liebig University Giessen (My University, 2010)
Chicks of burrowing petrels use begging calls to advertise their hunger levels when parents arrived at the nest. In a previous study, adult thin-billed prions Pachyptila belcheri responded to higher begging call rates of their single chick by regurgitating larger meals. We tested whether acoustic parameters of begging call elements may also be involved in signalling. To describe variation in begging, we determined begging session parameters, namely the duration, number of calls and the mean and maximum rate of calling. We then digitised calls and carried out a semi-automatic extraction of six acoustic parameters of call elements, including mean and maximum acoustic frequency, the length of call elements and the location of the maximum frequency and amplitude within calls. Chicks showed strong individual differences in all parameters. While the session parameters were correlated with body condition and with the meal size the chick received, none of the acoustic parameters were related to body condition and provisioning. A cross-fostering experiment showed the same pattern, as only session parameters changed related to an experimentally altered body condition, while acoustical cues appear to play no role in signalling hunger levels. We suggest that this may be explained by the absence of sibling competition in these birds. As parents do not need to decide which chick to feed, immediate information on condition at the time of adult arrival may not be required.
Keywords: Parent–offspring communication; Signalling; Provisioning; Pachyptila belcheri; Seabirds; ddc:570; ddc:590